A model for improving the quality of cardiovascular assistants’ teaching-learning environment in Shahid Beheshti University of Medical Sciences - Noori Frothagh, Azam; Jamali, Akhtar; Gourchian, Nadergholi (Researcher Bulletin of Medical Sciences, 2024)
Background and Objective: Higher education, as a driving force for sustainable development has a strategic role in ensuring quality in the society. Thus, higher education is expected to play its crucial role in creation of change and innovation in an appropriate way to underpin the quality. The study aimed to provide a model for improving the quality of the teaching-learning environment for cardiovascular assistants at Shahid Beheshti University of Medical Sciences, Iran. Materials and Methods: After implementation of open and axial coding, due to the lack of specific standards and explicit measurable criteria, the nine components approved by the experts were considered as a basis for the formation of a "model for improving the quality of the teaching-learning environment". The questions were designed based on 9 components and 27 sub-components in the form of a researcher-made questionnaire to determine the current status of teaching-learning environment for cardiovascular assistants. Results: The results showed that the contribution of each component in improving the quality of teaching-learning environment based on factor load distribution. Also, the degree of appropriateness of the components was determined. Conclusions: The analysis of the current status of teaching-learning environment for cardiovascular assistants indicates that despite the relatively favorable situation with a positive trend, the proposed model can contribute to the betterment of the situation in policy-making, planning, training, evaluation and resource development among cardiology human capital.